Development of an AIDS vaccine using Sendai virus vectors - Ishii, Hiroshi; Matano, Tetsuro (Vaccine, 2015)
Development of an effective AIDS vaccine is crucial for the control of global human immunodeficiency virus type 1 (HIV-1) prevalence. We have developed a novel AIDS vaccine using a Sendai virus (SeV) vector and investigated its efficacy in a macaque AIDS model of simian immunodeficiency virus (SIV) infection. Its immunogenicity and protective efficacy have been shown, indicating that the SeV vector is a promising delivery tool for AIDS vaccines. Here, we describe the potential of SeV vector as a vaccine antigen delivery tool to induce effective immune responses against HIV-1 infection.